Treatment of a Non-Healing Diabetic Foot Ulcer With Platelet-Rich Plasma - Suresh, Deepak H (J Cutan Aesthet Surg, 2014)
Lower extremity ulcers and amputations are an increasing problem among individuals with diabetes. Among diabetes mellitus-related complications, foot ulceration is the most common, affecting approximately 15% of diabetic patients during their lifetime. The pathogenesis of diabetic ulcer is peripheral sensory neuropathy, calluses, oedema and peripheral vascular disease. Diabetic ulcer is managed by adequate control of infections and blood sugar levels, surgical debridement with various dressings and off loading of the foot from pressure. In spite of these standard measures, some recalcitrant non-healing ulcers need additional growth factors for healing. Autologous platelet-rich plasma is easy and cost-effective method in treating diabetic ulcers as it provides necessary growth factors which enhance healing.